Youth mentoring and multiple social support attunement: Contributions to understand youth social development and well-being - Simões, F. (2022)
Youth mentoring is well-known to be a complex, hybrid relational context mirroring other interpersonal relationships characteristics. Mentoring blends features of parenting, such as care giving or role modelling, friendships, including mutuality or promoting a sense of belonging, or teaching, when it involves some degree of instruction. Youth mentoring intricacy goes beyond the replication of core attributes of other relational dyads. Youth mentors nurture and sustain their bonds with the mentees in a broader social ecology of co-occurring, interactive, and sometimes competing relationships (Keller, 2005; Varga & Zaf, 2017). The social ecology of relationships as a determining factor of youth mentoring quality is, however, a relatively novel topic. Dominant research eforts in youth mentoring literature have focused on understanding how categories of factors, such as mentees’ and mentors’ interpersonal history and social competencies to held and sustain a mentoring relationship, the infuence of developmental features on youth mentoring quality, relationship traits (e.g. duration), or programmes’ characteristics and implementation (relationships goals, activities, or closure) afect mentoring processes and outcomes.